INTEGRATIVE NUTRITIONAL ASSESSMENT EPIGENETICS TRANSGENERATIONAL EFFECTS AND LIFE HISTORY THEORY - Jefferson, Jadir (Health and Society, 2024)
This review describes how nutritional assessment and anamnesis questionnaires can be helped by information from research that addresses transgenerational epigenetic effects and life history theory (LHT) in the prevention and treatments of chronic non-communicable diseases (NCDs). The connection between these fields of biological studies allows for better preventive clarification of individual needs through interaction: environment, epigenetics, life strategy pathways and their impacts on the organism’s functions, such as growth, maintenance, reproduction and immunological defense, associated with risks that predispose to chronic diseases.